Analysis of the Publications on Ontology-Based Smart Grid Applications: A Birds Eye View - Mahmoud M.A.; Maseleno A.; Tang A.Y.C.; Lim F.-C.; Kasim H.B.; Yong C. (Springer, 2023)
Electric power transmission networks; Engineering research; Interoperability; Paper; Smart power grids; Surveys; Elsevier; Ontology-based; Research studies; Smart grid; Smart grid applications; Systematic Review; Ontology